2019
DOI: 10.15570/actaapa.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Non-ablative radio frequency for the treatment of androgenetic alopecia

Abstract: Subjects completed the study with an average of 3.63 sessions. The average increase in hair counts from baseline in the treatment group was higher than the placebo group 22.8% vs 9.6% (p = 0.08).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Some of the results described above coincide with those of some studies that have applied RF electrical therapies for the treatment of alopecia. In a single blinded study carried out in a sample of 24 men, the application of non-ablative RF currents increased hair growth compared to the untreated group [21]. Another study with 19 male subjects diagnosed with androgenic alopecia has shown an improvement in the efficacy of the combined treatment of 1 MHz of bipolar RF currents and minoxidil compared to treatment with minoxidil alone [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the results described above coincide with those of some studies that have applied RF electrical therapies for the treatment of alopecia. In a single blinded study carried out in a sample of 24 men, the application of non-ablative RF currents increased hair growth compared to the untreated group [21]. Another study with 19 male subjects diagnosed with androgenic alopecia has shown an improvement in the efficacy of the combined treatment of 1 MHz of bipolar RF currents and minoxidil compared to treatment with minoxidil alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…For the calculation of the sample size, data on sizes previously used for other similar studies were used [21,22,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It uses high frequency alternating current to produce a controlled increase in tissue temperature with the goal of inducing thermal damage to stimulate changes in collagen conformation and new collagen formation in deep layers of the skin and subcutaneous tissue 9 . A previous single‐blinded study comparing a nonablative fractional RF device and a sham device observed a larger increase in hair growth among patients in the treatment group, though results did not reach significance due to the small sample size 10 . Another single center, single‐blinded prospective study showed increases in both hair counts and hair shaft thickness with use of a fractional RF device 11 .…”
Section: Introductionmentioning
confidence: 99%